2001
DOI: 10.1046/j.0007-1323.2001.01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain and quality of life following open inguinal hernia repair

Abstract: Chronic pain occurred in 30 per cent of patients after open hernia repair, a higher frequency than has been reported previously. Several risk factors were identified and further prospective research is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

27
219
4
20

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(270 citation statements)
references
References 7 publications
27
219
4
20
Order By: Relevance
“…These findings are supported by our previous study in women undergoing gynecological surgery where all domains (except general health) and the two component scores improved six months after surgery. 23 Other reports have shown differences in HRQOL (social functioning, mental health, and pain) between those with and without chronic pain 24 and reduced HRQOL after several types of surgery, including inguinal hernia repair. 3,25 Compared with age-and sex-matched norms in the general population, we found that the general surgery cohort experienced lower levels of HRQOL (physical functioning, role-physical, general health, vitality, social functioning, and the PCS and MCS), and these scores remained well below Canadian norms six months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by our previous study in women undergoing gynecological surgery where all domains (except general health) and the two component scores improved six months after surgery. 23 Other reports have shown differences in HRQOL (social functioning, mental health, and pain) between those with and without chronic pain 24 and reduced HRQOL after several types of surgery, including inguinal hernia repair. 3,25 Compared with age-and sex-matched norms in the general population, we found that the general surgery cohort experienced lower levels of HRQOL (physical functioning, role-physical, general health, vitality, social functioning, and the PCS and MCS), and these scores remained well below Canadian norms six months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Ancak VKİ artışı ile kronik ağrı arasında ilişki saptamayan çalışmalar da bulunmaktadır. [9,14] Çalışmamızda; obezlerde kronik ağrı insidansı daha yüksek oranda görülmekle birlikte istatistiksel olarak anlamlı bir ilişki saptanmadı.…”
Section: Discussionunclassified
“…[3,14] Çalışmamızda; medeni durumun, bir işte çalışıyor ya da işsiz olmanın ameliyat sonrası kronik ağrı gelişiminde risk faktörü olmadığını saptadık.…”
Section: Discussionunclassified
“…In the present series groin pain was reported by 6% to 20% of patients in different techniques in early stage (up to 6-8 weeks) which settled and by the end of 2 years groin pain One patient had persistent erectile dysfunction in this review which is not new (22). Men frequently complain of impotence in the immediate aftermath of a hernia repair [24].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain has been reported to occur in up to 25-30% of patients after open inguinal hernia repair [20][21][22] This has obvious cost implications for the health service as well as the economy as a whole.…”
Section: Discussionmentioning
confidence: 99%